Development of myoglobin stores in skeletal muscles of hooded seal (Cystophora cristata) pups - Geiseler, Samuel J. (Universitetet i Tromsø, 2011)
The hooded seal is a deep diving phocid seal in the North Atlantic Ocean, possessing the highest oxygen storing capacity and the shortest lactation period of any mammal hitherto reported. Pups are not born expert divers and have to develop relevant physiological adaptations quickly in order to forage independently. To investigate the early development of myoglobin (Mb), a key molecule for diving adaptation, muscles from weaned hooded seal pups were sampled for a period of three months. This revealed a rapid initial rise of Mb levels within the first month accounting for 50 % of the Mb development of the entire first year of life. This developmental pattern coincides with the increase of dive duration of free living hooded seal pups, suggesting that the Mb level influences their diving behavior. To investigate if activity regulates Mb production, the swimming muscle M. longissimus dorsi and flipper muscle M. supraspinatus were examined as well as key enzymes for muscular metabolism. This showed that active muscles develop faster and have higher Mb concentrations than idle muscles whereas there is no difference in muscles of similar activity. This suggests that activity rather than hypoxia is influencing the post natal increase of Mb in seals.